Preparation method and application of cobalt-based metal organic framework (ZIF-67) confined growth monolithic porous carbon based on persulfate etching

CN122930738APending Publication Date: 2026-10-16CHINA UNIV OF MINING & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611048295.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,松木自身的管胞结构形成的孔道相对光滑,内腔中配位位置不足,导致木材与ZIF之间的相互作用较弱,在木材细胞壁上实现的ZIF负载量低且容易聚集和不均匀,阻碍了其作为高性能碳电极的使用

Benefits of technology

[0019] 1. Pore Reconstruction and Interface Activation via PMS Chemical Etching: This invention is the first to employ a potassium persulfate (PMS) system for chemical etching pretreatment of pine wood. PMS generates strong oxidizing free radicals through a Fenton-like reaction, selectively degrading lignin and hemicellulose in pine wood, disrupting the dense interwoven structure on the pore surface, and constructing hierarchical pores within the pine tracheids. Simultaneously, PMS etching introduces a large number of oxygen-containing functional groups (such as -OH and -COOH) into the inner walls of the pores, providing a high density of nucleation anchoring sites for the subsequent growth of ZIF-67. This synergistic mechanism of "pore reconstruction-interface activation" effectively improves the interfacial compatibility between pine wood and ZIF-67.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930738A_ABST
    Figure CN122930738A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of supercapacitor energy storage electrode material preparation, in particular to a preparation method and application of a whole-type porous carbon prepared by etching and inducing cobalt-based metal organic framework (ZIF-67) based on persulfate, which comprises the following steps: vacuum-assisted impregnation of pine wood pieces in a cobalt salt solution, chemical etching and surface reconstruction in a potassium hydrogen persulfate solution, secondary impregnation in a cobalt salt solution, transfer to a mixed solution containing dimethyl imidazole, potassium nitrate and sodium nitrate to induce in-situ confined growth of ZIF-67, and finally, segmented high-temperature carbonization to obtain the whole-type porous carbon. Through the "channel reconstruction-interface activation" synergistic mechanism of PMS, oxygen-containing functional groups are introduced into the inner wall of the pine wood channels as nucleation anchor points, the high loading capacity and uniform growth of ZIF-67 are realized, the specific surface area and pore structure are significantly improved, excellent electrochemical energy storage performance is exhibited, and the application is suitable for supercapacitor energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of supercapacitor energy storage electrode material preparation technology, specifically a method and application for preparing monolithic porous carbon based on persulfate etching-induced cobalt-based metal-organic framework (ZIF-67). Background Technology

[0002] With the global energy crisis and environmental problems becoming increasingly prominent, energy storage devices are a key hub for renewable energy power generation and end-use applications. Supercapacitors, due to their advantages such as high power density, fast charging and discharging, and stable cycling, have broad application prospects in fields such as new energy vehicles. Traditional carbon electrodes use a composite system of "active material-binder-conductive agent" coated onto the current collector, which has inherent drawbacks such as the binder reducing conductivity, hindering electrolyte contact, and occupying energy storage space. Integral carbon electrodes (or self-supporting carbon electrodes) eliminate the need for binders and current collectors, and by leveraging their own three-dimensional porous structure to optimize electron transport and electrolyte wetting paths, they are expected to simultaneously improve the energy storage performance of supercapacitors.

[0003] Pine wood, as a widely available and inexpensive biomass raw material, is an excellent precursor for the preparation of monolithic carbon electrodes. After carbonization, metal-organic frameworks (such as ZIF-67) form porous N-doped frameworks, and the combination of wood and ZIF can produce carbon electrodes with high energy density. However, the pores formed by the tracheal structure of pine wood are relatively smooth, and there are insufficient coordination sites in the lumen, resulting in weak interaction between wood and ZIF. The ZIF loading achieved on the wood cell walls is low, prone to aggregation, and uneven, hindering its use as a high-performance carbon electrode. Therefore, to address these shortcomings, there is an urgent need to develop a method and application for the preparation of monolithic porous carbon based on persulfate etching-induced confined growth of cobalt-based metal-organic frameworks (ZIF-67) to overcome the deficiencies in current practical applications. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method and application for preparing monolithic porous carbon based on persulfate etching-induced cobalt-based metal-organic framework (ZIF-67) confined growth.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] A method for preparing monolithic porous carbon based on persulfate etching-induced cobalt-based metal-organic framework (ZIF-67) confined growth includes the following steps:

[0007] Step 1: Cut the pine wood into pine chips along the growth direction, and place the pine chips in a cobalt salt solution for vacuum-assisted impregnation to obtain pre-impregnated pine chips;

[0008] Step 2: The pre-impregnated pine chips are placed in a potassium persulfate (PMS) solution for chemical etching to degrade some of the dense components and introduce oxygen-containing functional groups. They are then washed until neutral and dried to obtain oxidized reconstituted pine chips.

[0009] Step 3: The oxidized and reconstituted pine chips are immersed in cobalt salt solution again, and then transferred to a mixed solution containing dimethylimidazolium (2-MIM), potassium nitrate and sodium nitrate. Relying on the oxygen-containing functional groups on the surface of the pores as nucleation anchors, ZIF-67 is induced to grow in situ within the pores. After washing and drying, pine chips loaded with ZIF-67 are obtained.

[0010] Step 4: The ZIF-67-loaded pine wood chips are subjected to segmented high-temperature carbonization treatment under an inert atmosphere. After washing and drying, the product is used to obtain an integral porous carbon with a strong coupling between a ZIF-67-derived Co-C porous network and a pine wood-derived carbon skeleton.

[0011] As a further aspect of the present invention: in step 1, the cobalt salt solution is a cobalt nitrate solution with a concentration of 0.25 mol / L; the vacuum-assisted impregnation time is 60 min, and the gas is evacuated and released once every 10 minutes.

[0012] As a further aspect of the present invention: in step 2, the concentration of the potassium persulfate (PMS) solution is 0.32 g / mL, and the chemical etching treatment is performed at room temperature for 12-24 h.

[0013] As a further aspect of the present invention: in step 3, the solvent of the mixed solution is a mixture of ethanol and water with a volume ratio of 1:1; the concentration of dimethylimidazole (2-MIM) in the mixed solution is 0.25 mol / L, the molar ratio of potassium nitrate to cobalt nitrate in step 1 is 1:1, and the sum of the mass concentrations of potassium nitrate and sodium nitrate does not exceed 7 g / 100 mL; the growth temperature of ZIF-67 is controlled at 25-35℃, and the growth time is 24 h.

[0014] As a further aspect of the present invention: in step 4, the inert atmosphere is nitrogen, and the flow rate is 200-600 mL / min; the heating program for the segmented high-temperature carbonization treatment is as follows: heat to 300°C at a heating rate of 5°C / min and hold for 60-90 min, then continue heating to 900°C at a heating rate of 5°C / min and hold for 60-180 min.

[0015] As a further aspect of the present invention: the washing and drying in step 4 specifically involves: placing the carbonized product in deionized water for ultrasonic washing, polishing it to a thickness of 0.8 mm using a 2000-mesh abrasive stone, placing it in deionized water for ultrasonic cleaning again, and then drying it at 80°C.

[0016] This invention also provides a monolithic porous carbon prepared by the above method, wherein the monolithic porous carbon is composed of a pine-derived carbon framework coupled with a Co-C nanoporous structure supported thereon; its specific surface area is not less than 438.4 m². 2 / g, microporous specific surface area not less than 352.5m² 2 / g.

[0017] This invention further provides the application of the above-mentioned monolithic porous carbon as an electrode material for supercapacitors. In a preferred embodiment, the supercapacitor is a symmetrical supercapacitor, and the monolithic porous carbon serves as both the positive and negative electrode.

[0018] Compared with the prior art, the beneficial effects of the present invention are:

[0019] 1. Pore Reconstruction and Interface Activation via PMS Chemical Etching: This invention is the first to employ a potassium persulfate (PMS) system for chemical etching pretreatment of pine wood. PMS generates strong oxidizing free radicals through a Fenton-like reaction, selectively degrading lignin and hemicellulose in pine wood, disrupting the dense interwoven structure on the pore surface, and constructing hierarchical pores within the pine tracheids. Simultaneously, PMS etching introduces a large number of oxygen-containing functional groups (such as -OH and -COOH) into the inner walls of the pores, providing a high density of nucleation anchoring sites for the subsequent growth of ZIF-67. This synergistic mechanism of "pore reconstruction-interface activation" effectively improves the interfacial compatibility between pine wood and ZIF-67.

[0020] 2. Achieving High Loading and Uniform In-situ Confined Growth of ZIF-67: Compared to unoxidized pine chips (Co-CW), PMS oxidation pretreatment significantly increased the number of active sites on the pine wood pore surface, inducing high loading and uniform in-situ confined growth of ZIF-67 within the tracheids. SEM and EDS characterization confirmed that the loading of ZIF derivatives in the Co-OCW samples was significantly increased and uniformly distributed, with Co and N elements evenly distributed on the surface of the wood chips, effectively avoiding the aggregation problem of ZIF-67 particles.

[0021] 3. Significantly improved specific surface area and pore structure: Compared with the unoxidized control group (Co-CW), the monolithic porous carbon (Co-OCW) prepared by PMS oxidation assistance showed a significantly increased specific surface area of ​​174.3 m². 2 / g jumped significantly to 438.4m 2 / g, the specific surface area of ​​the micropores increased from 143.5m². 2 / g increased to 352.5m 2 / g. The highly developed hierarchical porous network provides abundant active sites and rapid diffusion channels for ion transport and charge storage.

[0022] 4. Excellent electrochemical energy storage performance: The monolithic porous carbon electrode prepared by this invention exhibits excellent electrochemical performance in a three-electrode system: at 5 mA / cm²... 2 At current density, the areal capacitance reaches 6.44 F / cm². 2 The unoxidized control group had a ratio of only 3.31 F / cm. 2 When the current density increases to 50 mA / cm 2 At that time, it still maintained 5.05F / cm 2 It has a high specific capacity and a rate performance of 78.4%; the CV curve is approximately a standard rectangle, indicating that the electrode has good double-layer behavior and charge-discharge reversibility.

[0023] 5. Excellent performance of symmetrical supercapacitors: Symmetrical supercapacitors assembled with Co-OCW (Co-OCW / / Co-OCW) exhibit excellent device performance: at 5mA / cm 2 At the current density, the highest energy density is 296 μWh / cm³. 2 (Power density 2.5mW / cm³) 2 ); at 25mW / cm 2 Even at high power densities, the energy density remains at 225 μWh / cm³. 2 After 10,000 charge-discharge cycles, the capacitance retention rate reached 95.3%, demonstrating excellent cycle stability and practical application potential.

[0024] 6. Simple preparation process and widely available raw materials: This invention uses pine wood as a carbon precursor, which is widely available and inexpensive. The monolithic carbon electrode eliminates the need for binders and current collectors, avoiding the conductivity degradation and energy storage space occupation problems caused by binders in traditional electrode preparation. This method is simple, easy to scale up, and has good industrialization prospects. Attached Figure Description

[0025] Figure 1 This is a flowchart illustrating the preparation process of the monolithic porous carbon of the present invention.

[0026] Figure 2 The images show the morphological SEM images of the sample without PMS oxidation (Co-CW) and the sample with PMS oxidation (Co-OCW) of this invention.

[0027] Figure 3 This is a comparison of the XRD spectra of different samples from this invention.

[0028] Figure 4 A comparison of Raman spectra of different samples from this invention.

[0029] Figure 5 The isotherms for N2 adsorption and desorption of different samples in this invention are shown.

[0030] Figure 6 This is a comparison of the pore size distribution of different samples in this invention.

[0031] Figure 7 The CV curves for CW, Co-CW, and Co-OCW scans of this invention are shown at a scan rate of 10 mV / s.

[0032] Figure 8 The GCD curves for CW, Co-CW, and Co-OCW current densities of the present invention are shown at 5 mA / cm².

[0033] Figure 9 The CV curves for the Co-OCW scan rate of this invention are shown below when the scan rate is 1-20 mV / s.

[0034] Figure 10 The GCD curves of the Co-OCW of this invention at different current densities are shown.

[0035] Figure 11 The EIS curves for Co-CW and Co-OCW of this invention are shown.

[0036] Figure 12 The areal ratio capacitance of OCW, Co-CW and Co-OCW under different current densities in this invention.

[0037] Figure 13 The CV curves of the supercapacitor constructed using the Co-OCW method of this invention at different scan rates.

[0038] Figure 14 The GCD curves of the supercapacitor constructed using the Co-OCW method of this invention under different current densities are shown.

[0039] Figure 15 The areal capacitance of the supercapacitor constructed by Co-OCW in this invention under different current densities.

[0040] Figure 16 The EIS curve of the supercapacitor constructed using the Co-OCW method of this invention.

[0041] Figure 17 The stability of the supercapacitor constructed by Co-OCW in this invention after 10,000 cycles.

[0042] Figure 18 The adsorption-desorption curves of carbon materials in PMS samples of different concentrations are shown.

[0043] Figure 19 CV curves for carbon materials with different PMS concentrations. Detailed Implementation

[0044] The technical solution of this application will be further described in detail below with reference to specific embodiments.

[0045] The embodiments of this application are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0046] Example 1 (Sample Preparation)

[0047] according to Figure 1 The process shown is for preparing monolithic porous carbon (Co-OCW), and the specific steps are as follows:

[0048] (1) Raw material preparation and vacuum-assisted impregnation

[0049] Pine wood was cut into thin slices measuring 1.5mm × 1.5mm × 0.14mm along its growth direction to obtain the initial raw material for the experiment.

[0050] Dissolve 20 mmol of Co(NO3)2·6H2O in 40 mL of deionized water to prepare a 0.25 mol / L cobalt nitrate solution. Add pine wood chips to the cobalt nitrate solution and impregnate under vacuum for 60 min, with the vacuum cycled every 10 min (vacuuming and venting refer to restoring atmospheric pressure after vacuuming to ensure the solution fully wets the internal pores of the pine wood chips). This yields pre-impregnated pine wood chips and the original cobalt nitrate solution (to be reserved for later use).

[0051] (2) PMS chemical etching and surface reconstruction

[0052] To prepare a potassium persulfate (PMS) aqueous solution: Dissolve 12.8 g of PMS in 40 mL of deionized water to obtain a concentration of 0.32 g / mL.

[0053] Pre-impregnated pine chips were placed in PMS solution and left to stand overnight (12-24 h) at room temperature for thorough etching. After removal, they were washed with deionized water until neutral (pH of the wash solution was 6.5-7.5 as tested with pH paper), and dried to obtain oxidized reconstituted pine chips (OW).

[0054] (3) In-situ confined growth of ZIF-67

[0055] The oxidized and reconstituted pine chips were placed back into the cobalt nitrate stock solution after impregnation in step (1) and shaken for 12 hours.

[0056] The impregnation product was then transferred to a mixed solution containing dimethylimidazole (2-MIM), potassium nitrate, and sodium nitrate. The solvent for this mixed solution was a 1:1 volume ratio of ethanol / water (total volume 80 mL), wherein: the concentration of 2-MIM was 0.25 mol / L (i.e., 20 mmol); the amount of KNO3 added was 3.042 g; the amount of NaNO3 added was 2.558 g; and the molar ratio of potassium nitrate to cobalt nitrate in step (1) was 1:1.

[0057] Calculations show that when 3.042 g KNO3 and 2.558 g NaNO3 are dissolved in 80 mL of a mixed solution, the sum of their mass concentrations is approximately 7.0 g / 100 mL, which meets the preferred range of not exceeding 7 g / 100 mL.

[0058] The entire system was left to stand at 30°C for 24 hours to induce in-situ confined growth of ZIF-67 within the pores of the pine wood. After growth was complete, the pine wood chips were removed and washed four times with anhydrous ethanol (KNO3 and NaNO3 were retained during this process due to their different solubilities). The chips were then weighed down and dried in an oven at 80°C for 6 hours to obtain oxidized pine wood chips loaded with ZIF-67 (ZIF-67 / OW).

[0059] (4) Segmented high-temperature carbonization

[0060] ZIF-67-loaded oxidized pine chips were placed in a tube furnace and subjected to segmented high-temperature carbonization under a nitrogen atmosphere. The nitrogen flow rate was 550 mL / min. The heating program was as follows: increase the temperature to 300℃ at 5℃ / min and hold for 60 min; then increase the temperature to 900℃ at 5℃ / min and hold for 120 min. After naturally cooling to room temperature, the chips were removed.

[0061] (5) Post-processing

[0062] The carbonized product was ultrasonically washed multiple times in deionized water, polished to a thickness of 0.8 mm with a 2000-mesh abrasive stone, and ultrasonically cleaned again in deionized water until no powder was left on the surface. It was then dried at 80°C for 24 hours to obtain monolithic porous carbon, denoted as Co-OCW.

[0063] (6) Preparation of control group samples

[0064] As a comparative experiment, in step (2), the 0.32 g / m L PMS solution was replaced with an equal volume of pure water, and the remaining steps were completely the same, to prepare a control group porous carbon sample without oxidation pretreatment, denoted as Co-CW.

[0065] In addition, following the same method described above, samples treated with different PMS concentrations were prepared with PMS addition amounts of 0 g, 3.2 g, 6.4 g, and 12.8 g (corresponding to concentrations of 0, 0.08 g / mL, 0.16 g / mL, and 0.32 g / mL in 40 mL of water, respectively), and were designated as Co-OCW-0, Co-OCW-3.2, Co-OCW-6.4, and Co-OCW-12.8, respectively.

[0066] Example 2 (PMS Concentration Optimization Experiment)

[0067] To determine the optimal PMS concentration, this invention investigated the effect of PMS addition on the material structure and electrochemical performance.

[0068] (1) Analysis of N2 adsorption-desorption curves

[0069] like Figure 18 As shown, the N2 adsorption-desorption curves of samples treated with different concentrations of PMS (Co-OCW-0, Co-OCW-3.2, Co-OCW-6.4, and Co-OCW-12.8) were analyzed. The results showed that the specific surface area of ​​the samples gradually increased as the PMS concentration increased from 0 to 0.32 g / mL. The Co-OCW-12.8 sample (PMS concentration 0.32 g / mL) exhibited the highest specific surface area and the most pronounced hysteresis loop, indicating that it possessed the most developed hierarchical porous structure. Too low a concentration (0.08, 0.16 g / mL) resulted in insufficient etching and limited pore reconstruction; too high a concentration may lead to over-etching, damaging the carbon framework structure.

[0070] (2) CV curve analysis

[0071] like Figure 19 As shown, the CV curves of samples treated with different concentrations of PMS all exhibit rectangular characteristics, indicating good double-layer capacitance behavior. Among them, the Co-OCW-12.8 sample has the largest integral area of ​​its CV curve, indicating that it has the highest specific capacitance.

[0072] (3) Determination of optimal concentration

[0073] Based on the combined results of the N2 adsorption-desorption curves and CV curves, the sample exhibited optimal pore structure characteristics and electrochemical performance when the PMS concentration was 0.32 g / mL (i.e., 12.8 g / 40 mL). Therefore, 0.32 g / mL was determined to be the optimal PMS concentration.

[0074] Example 3 (Materials Characterization)

[0075] The microstructure and crystal structure of the Co-OCW and Co-CW prepared in Example 1 were characterized.

[0076] (1) Scanning electron microscopy (SEM) analysis

[0077] like Figure 2 As shown, in the Co-CW sample without PMS treatment, the surface of the original pine wood vessels was relatively regular, the loaded material was fluffy, and ZIF-67 did not grow significantly. However, in the Co-OCW sample treated with 0.32 g / mL PMS, the surface of the pine wood pores was oxidized and modified, and the loading of ZIF derivatives increased significantly and was evenly distributed. EDS analysis further confirmed that C and O were characteristic elements of the charcoal substrate on the Co-OCW surface, while N and Co were uniformly distributed on the wood chip surface, proving that the ZIF-67 carbonization-derived Co-C porous structure was successfully and uniformly loaded onto the pine charcoal framework.

[0078] (2) X-ray diffraction (XRD) analysis

[0079] like Figure 3 As shown, all samples exhibit broad peaks of amorphous carbon; the diffraction peaks at 44.3° and 51.4° correspond to the (111) and (200) crystal planes of metallic Co, respectively, proving the successful loading of metallic Co.

[0080] (3) Raman spectroscopy analysis

[0081] like Figure 4 As shown, the ID / IG value of Co-OCW is 1.13, which is higher than that of Co-CW. This indicates that the PMS oxidation pretreatment breaks the original dense structure of pine wood, increases the disorder and defect sites of carbon materials, and is beneficial to ion adsorption and charge storage.

[0082] Example 4 (Pore Structure Analysis)

[0083] The N2 adsorption-desorption test was performed on the sample prepared in Example 1.

[0084] like Figure 5-6 As shown, all samples exhibited type IV isotherms and distinct hysteresis loops, indicating the presence of mesoporous structures. The specific surface area of ​​the unoxidized control group Co-CW was only 174.3 m². 2 / g, microporous specific surface area 143.5m² 2 / g. The specific surface area of ​​Co-OCW treated with 0.32 g / mL PMS increased significantly to 438.4 m². 2 / g, the specific surface area of ​​micropores increased to 352.5m². 2 / g. This directly demonstrates the effective destructive effect of PMS oxidation pretreatment on the dense biomass matrix surface. The abundant oxygen-containing functional groups assist and promote the large-scale, uniform in-situ growth of ZIF-67, thereby constructing a highly developed porous network and electrochemical active sites after carbonization.

[0085] Example 5 (Electrochemical Performance Test)

[0086] (1) Three-electrode system test

[0087] In a three-electrode testing system, at a scan rate of 10 mV / s, the CV curves of CW, Co-CW, and Co-OCW are compared as follows: Figure 7 As shown in the figure, the Co-OCW exhibits the largest area of ​​integration in its CV curve, indicating that the specific capacitance of the material is significantly improved after PMS oxidation treatment and loading with ZIF-67.

[0088] When the scan rate is 1-20 mV / s, the CV curve of Co-OCW is approximately a standard rectangle. Figure 9 This indicates that the monolithic porous carbon electrode exhibits excellent double-layer behavior and superior charge-discharge reversibility.

[0089] Constant current charge-discharge (GCD) test Figure 8 , Figure 10 This indicates that at 5mA / cm 2 At current density, the areal capacitance of Co-OCW reaches 6.44 F / cm². 2 While Co-CW is only 3.31 F / cm 2 When the current density increases significantly to 50 mA / cm 2 At that time, Co-OCW still maintained 5.05F / cm 2 It has a high specific capacity and a rate performance of 78.4%.

[0090] (2) Repeatability verification

[0091] To verify the reproducibility of electrochemical performance, two batches of Co-OCW samples were prepared independently and their performance at 5 mA / cm² was tested. 2 Area ratio capacitance under current density.

[0092] The test results are as follows:

[0093] Co-OCW (oxidation group): The results of the two tests were 6.59 F / cm. 2 and 6.29F / cm 2 The average value is 6.44 F / cm. 2 Deviation ±0.15F / cm 2 (Relative deviation ±2.3%)

[0094] Co-CW (unoxidized control group): The results of the two tests were 3.39 F / cm. 2 and 3.23F / cm 2 The average value is 3.31 F / cm. 2 Deviation ±0.08F / cm 2 (Relative deviation ±2.4%).

[0095] The relative deviations of the two groups of samples were both less than ±3%, indicating that the monolithic porous carbon material prepared by this invention has good batch reproducibility and test stability.

[0096] (3) Performance of symmetrical supercapacitors

[0097] To evaluate its practical application potential, a symmetrical supercapacitor (Co-OCW / / Co-OCW) was constructed using PMS-oxidized Co-OCW samples. It achieved a capacitance of 5 mA / cm². 2 The highest energy density at current density is 296 μWh / cm³. 2 The power density is 2.5 mW / cm³. 2 At 25mW / cm 2 Even at high power densities, the energy density remains at 225 μWh / cm³. 2 ( Figure 13-16 ).

[0098] At 50mA / cm 2 10,000 charge-discharge cycles were performed at current density. Figure 17 With a capacitance retention rate as high as 95.3%, it demonstrates excellent device cycle stability and industrialization prospects.

[0099] Example 6 (Basis for parameter determination and explanation of mechanism)

[0100] (1) Basis for determining carbonization temperature

[0101] Carbon materials for supercapacitors need to possess both sufficient graphitization and high specific surface area. Literature review and preliminary experiments have shown that a carbonization temperature within the range of 800-1000℃ yields good overall performance. At temperatures below 800℃, graphitization is insufficient, resulting in poor conductivity; at temperatures above 1000℃, the specific surface area decreases. This invention selects 900℃ as the carbonization temperature, at which the optimal balance between graphitization and specific surface area is achieved.

[0102] (2) Mechanism of action of potassium nitrate and sodium nitrate

[0103] The present invention simultaneously adds potassium nitrate and sodium nitrate to the ZIF-67 growth system, mainly for the following purposes:

[0104] 1. Both are selectively retained in the system due to their solubility differences during the ethanol / water mixed solvent and subsequent anhydrous ethanol washing process, thus continuously regulating the ionic strength of the solution;

[0105] 2. Moderate ionic strength can inhibit homogeneous nucleation of ZIF-67 in solution and promote heterogeneous nucleation at oxygen-containing functional group sites on the surface of pine wood pores, thereby achieving "in-situ confined growth".

[0106] 3. In addition, potassium nitrate and sodium nitrate also play a role in activating biochar during the high-temperature carbonization process, which helps to create pores and further increase the specific surface area.

[0107] The total salt concentration was controlled to be below 7g / 100mL in order to avoid excessive ionic strength which would inhibit the growth of ZIF-67.

[0108] This invention relates to a method and application for preparing monolithic porous carbon based on the confined growth of a cobalt-based metal-organic framework (ZIF-67) induced by persulfate etching. The method employs a potassium persulfate (PMS) system to oxidize biomass wood. Through a Fenton-like reaction, highly oxidizing free radicals selectively degrade lignin and hemicellulose, disrupting the dense, interwoven structure of the wood pores and significantly increasing the number of micropores and mesopores. Compared to unoxidized pine chips, the addition of PMS for oxidation pretreatment introduces abundant oxygen-containing functional groups and increases active sites on the pine surface, thereby assisting and inducing the uniform growth of ZIF-67 on the pore walls, preventing ZIF-67 particle aggregation, and achieving a uniform distribution of Co and N elements on the monolithic carbon framework. The monolithic porous carbon prepared with PMS oxidation assistance exhibits a significantly increased specific surface area of ​​438.4 m² compared to the unoxidized substrate. 2 / g, with a microporous specific surface area reaching 352.5m². 2 / g, greatly increasing the charge storage space and electrochemical active sites of the material; the monolithic porous carbon electrode synthesized by this method exhibits excellent electrochemical performance, at 5mA / cm 2 The area capacitance at current density reaches 6.44 F / cm². 2 The rate capability reaches 78.4%. The assembled symmetrical supercapacitor achieves a rate capability of 25 mW / cm². 2 Energy density reaches 225 μWh / cm³ at power density 2 After 10,000 charge-discharge cycles, the capacitance retention rate reached 95.3%, demonstrating excellent cycle stability and practical application potential.

[0109] The above are merely preferred embodiments of the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention, and these should also be considered within the scope of protection of the present invention. These will not affect the effectiveness of the implementation of the present invention or the practicality of the patent.

Claims

1. A method for preparing monolithic porous carbon based on persulfate etching-induced cobalt-based metal-organic framework (ZIF-67) confined growth, characterized in that, Includes the following steps: Step 1: Cut the pine wood into pine chips along the growth direction, and place the pine chips in a cobalt salt solution for vacuum-assisted impregnation to obtain pre-impregnated pine chips; Step 2: The pre-impregnated pine chips are placed in a potassium persulfate (PMS) solution for chemical etching to degrade some of the dense components and introduce oxygen-containing functional groups. They are then washed until neutral and dried to obtain oxidized reconstituted pine chips. Step 3: The oxidized and reconstituted pine chips are immersed in cobalt salt solution again, and then transferred to a mixed solution containing dimethylimidazolium (2-MIM), potassium nitrate and sodium nitrate. Relying on the oxygen-containing functional groups on the surface of the pores as nucleation anchors, ZIF-67 is induced to grow in situ within the pores. After washing and drying, pine chips loaded with ZIF-67 are obtained. Step 4: The ZIF-67-loaded pine wood chips are subjected to segmented high-temperature carbonization treatment under an inert atmosphere. After washing and drying, the product is used to obtain an integral porous carbon with a strong coupling between a ZIF-67-derived Co-C porous network and a pine wood-derived carbon skeleton.

2. The method for preparing monolithic porous carbon based on persulfate etching-induced cobalt-based metal-organic framework (ZIF-67) confined growth according to claim 1, characterized in that, In step 1, the cobalt salt solution is a cobalt nitrate solution with a concentration of 0.25 mol / L; the vacuum-assisted impregnation time is 60 min, and the gas is evacuated and released once every 10 minutes.

3. The method for preparing monolithic porous carbon based on persulfate etching-induced cobalt-based metal-organic framework (ZIF-67) confined growth according to claim 1, characterized in that, In step 2, the concentration of the potassium persulfate (PMS) solution is 0.32 g / mL, and the chemical etching process is carried out at room temperature for 12-24 h.

4. The method for preparing monolithic porous carbon based on persulfate etching-induced cobalt-based metal-organic framework (ZIF-67) confined growth according to claim 1, characterized in that, In step 3, the solvent of the mixed solution is a mixture of ethanol and water with a volume ratio of 1:1; the concentration of dimethylimidazole (2-MIM) in the mixed solution is 0.25 mol / L, the molar ratio of potassium nitrate to cobalt nitrate mentioned in step 1 is 1:1, and the sum of the mass concentrations of potassium nitrate and sodium nitrate does not exceed 7 g / 100 mL; the growth temperature of ZIF-67 is controlled at 25-35℃, and the growth time is 24 h.

5. The method for preparing monolithic porous carbon based on persulfate etching-induced cobalt-based metal-organic framework (ZIF-67) confined growth according to claim 1, characterized in that, In step 4, the inert atmosphere is nitrogen, and the flow rate is 200-600 mL / min; the heating program for the segmented high-temperature carbonization treatment is as follows: heat to 300℃ at a heating rate of 5℃ / min and hold for 60-90 min, then continue heating to 900℃ at a heating rate of 5℃ / min and hold for 60-180 min.

6. The method for preparing monolithic porous carbon based on persulfate etching-induced cobalt-based metal-organic framework (ZIF-67) confined growth according to claim 1, characterized in that, The washing and drying process described in step 4 is as follows: the carbonized product is placed in deionized water for ultrasonic washing, polished to a thickness of 0.8 mm using a 2000-grit abrasive stone, ultrasonically cleaned again in deionized water, and then dried at 80°C.

7. The monolithic porous carbon prepared by the preparation method according to any one of claims 1 to 6, characterized in that, The monolithic porous charcoal is composed of a pine-derived carbon framework coupled with a Co-C nanoporous structure supported thereon; its specific surface area is not less than 438.4 m². 2 / g, microporous specific surface area not less than 352.5m² 2 / g.

8. The application of the monolithic porous carbon as described in claim 7 as an electrode material for supercapacitors.

9. The application according to claim 8, characterized in that, The supercapacitor is a symmetrical supercapacitor, and the monolithic porous carbon serves as both the positive and negative electrode.